Cultural Shifting And Non-Verbal Communication Reconstruction In Covid-19 Outbreak: Indonesia’S Insight - Yuliana Rakhmawati (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
COVID 19 has had a multidisciplinary impact on health, economic, and socio-political emergencies. In the context of communal culture, the impact is increasingly felt. Various activities that prioritize collectivity become limited and even eliminated. In general, communal people used to handle certain messages with physical touch. During the pandemic, conversely, non-verbal activity are in a shifting mode. Therefore, this research attempt to identifies interaction patterns changes in collective society addressing the new habit in non-verbal communication perspectives. This research uses literature studies on journals, previous studies, and other textual documents that are relevant to the research objectives. The analysis results were discussed by the Birdwhistell kinesics theory and Hall's proxemics theory. The research obtained the discussion about non-verbal communication patterns shifting from the haptic tradition to mediated communication. Furthermore, the discussion also apply to physical distance in space and time theory outlook. Therefore, in collective society, the changes will not only generate a new culture but also deliver the way of thinking shifting. The communication barriers presence in indexical signs use then likely happened. Further research could emphasize on macro levels in language relativity perspective. The use of positivistic paradigms to explain correlations between population characteristics and changes in communication behavior patterns during a pandemic can also be explored.